A shield tail grease adhesion performance testing method and device
By using constant temperature pretreatment and control pressure in the shield tail grease test, the adhesion plate is bonded to the test board, combined with infrared detection and magnetic propulsion ply, the adhesion force is calculated, and the lack of reliability of the test results in the existing technology is solved. The problem of this problem has achieved high accuracy and high repeatability test results, which is suitable for the quality evaluation of shield tail grease products.
Patent Information
- Application Number
- CN202410978629.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-07-22
AI Technical Summary
The existing shield tail grease adhesion testing device cannot accurately simulate the pressure conditions during construction, resulting in insufficient accuracy and repeatability of the detection data, affecting the reliability of actual applications.
Provide a method for testing the adhesion performance of shield-shaped shield tail grease. Through constant temperature pretreatment and control pressure, the adhesive plate is bonded to the test plate, the sliding time is recorded, the adhesion force is calculated based on the formula, and infrared detection device and magnetic propulsion ply are used. , repeated tests and remove extreme values to improve the reliability of the results.
It improves the accuracy and repeatability of shield tail grease adhesion tests, simplifies the testing process, reduces equipment costs, and enhances the reliability of test results. It is suitable for large-scale applications and quality evaluation of shield tail grease products.
Smart Images

Figure CN118518580B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shield tail grease adhesion testing, in particular to a shield tail grease adhesion performance testing method and a device thereof. Background Art
[0002] Shield construction technology has been widely used in rail and underground engineering construction, and shield tail sealing grease is one of the most important sealing materials. Therefore, excellent shield tail sealing grease is particularly important in shield construction. Its efficient sealing performance and good lubrication can effectively protect the shield tail, avoid collapse accidents, fully isolate groundwater and mud, and ensure the smooth progress of shield construction. Not only that, excellent shield tail sealing oil can also effectively prevent corrosion of the shield machine and avoid unnecessary wear. Therefore, the shield tail sealing grease should have good adhesion to the shield tail steel plate, wire brush, pipe segment, etc., and can be firmly adhered to the sealing device of the shield machine to ensure the sealing effect.
[0003] At present, most shield tail sealant grease manufacturers use manual adhesion test devices, which cannot truly simulate technical parameters such as pressure during shield construction, and the test data has large deviations. A Chinese patent (authorization announcement number is CN 217233503U) discloses a test device for the adhesion performance of shield tail grease. Although the test device simulates some parameters such as pressure under shield construction, the accuracy and repeatability of the test data of the device need to be further improved, and the simulated shield construction will inevitably come into contact with concrete during the actual construction process. Therefore, the reliability of the device used to characterize the adhesion of shield tail sealant grease on the metal plate surface when used in actual applications needs to be further improved. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for testing the adhesion performance of shield tail grease, which effectively overcomes the problem of low reliability of adhesion test results obtained by existing testing devices when used to characterize actual application conditions. The method is simple, easy to operate, highly accurate, and repeatable, and can be widely promoted and applied.
[0005] On the one hand, the present invention provides a method for testing the adhesion performance of grease at the tail of a shield machine, which at least comprises the following steps:
[0006] (1) Prepare the grease sample to be tested and the test device, and fix the test plate on the supporting back plate;
[0007] (2) Pre-treating the oil sample to be tested at a constant temperature and then scraping it onto the surface of the carrier plate to obtain an adhesive plate, and then fixing the adhesive plate on the advancing clamping plate;
[0008] (3) Control the pressure to make the adhesive plate fixed on the pushing clamp plate fit with the test plate fixed on the supporting back plate;
[0009] (4) Record the time it takes for the adhesive plate to slide off the surface of the test plate;
[0010] (5) Clean the adhesion plate and the test plate, repeat steps (2) to (5), and perform parallel tests 4 to 6 times;
[0011] (6) Extract valid data from the parallel test results and calculate the adhesion performance of the grease sample to be tested based on the formula.
[0012] As a preferred technical solution, the test plate is a metal plate and a concrete plate.
[0013] Preferably, the concrete slab is immersed in water until the surface is moistened before testing, and before the metal slab and the concrete slab are bonded to the adhesive plate, a water spray bottle is used to evenly wet the bonded side of the metal slab and the concrete slab to the adhesive plate.
[0014] As a preferred technical solution, the constant temperature pretreatment is: placing the oil sample to be tested in a constant temperature box and controlling the temperature to 15-30°C for at least 2 hours. Preferably, the constant temperature pretreatment is: placing the oil sample to be tested in a constant temperature box and controlling the temperature to 20±3°C for at least 3 hours.
[0015] As a preferred technical solution, the shape of the carrier plate and the test plate is preferably one of a cuboid, a cube, and a cylinder. Preferably, the carrier plate and the test plate have the same shape, both of which are cuboids.
[0016] As a preferred technical solution, the ratio of the area of the carrier plate to the bonding surface of the test plate is 1:(5-10), preferably 1:6.
[0017] As a preferred technical solution, the surface of the carrier plate is covered with the oil sample to be tested, and the area thereof accounts for more than 1 / 2 of the area of the carrier plate (circular coating drawn from the center of the carrier plate), preferably more than 4 / 5, and most preferably, the entire plate is covered and the thickness of the oil sample to be tested covered on the surface of the carrier plate is uniform.
[0018] As a preferred technical solution, the ratio of the mass of the oil sample to be tested covered on the surface of the carrier plate to the mass of the carrier plate is (1-3):(30-40), preferably 2:(30-40), and most preferably 2:35.
[0019] As a preferred technical solution, the adhesion plate and the propulsion splint are fixed by adsorption, specifically by magnetic adsorption.
[0020] As a preferred technical solution, the propulsion splint is a magnetic propulsion splint, and the material of the carrier plate is a material that can be adsorbed and fixed by the magnetic propulsion splint, preferably a steel plate.
[0021] As a preferred technical solution, the pressure in step (3) is controlled to be 6-8 kg, preferably 7±0.3 kg.
[0022] As a preferred technical solution, the lamination time in step (3) is 3-10 seconds, preferably 5 seconds.
[0023] As a preferred technical solution, the time for the adhesive plate to slide off the surface of the test plate is recorded by a timer connected to an infrared detection device. The timer starts at the time when the pressure is controlled to 0 after step (3) is completed, and the magnetic button of the push clamp is closed, so that the adhesive plate and the test plate are connected only by the adhesion force of the grease sample to be tested. After that, the adhesive plate and the test plate lose their surface viscosity and slide off the infrared detection device. At this time, the timing is stopped, and the time for the adhesive plate to slide off the surface of the test plate is obtained.
[0024] The infrared detection device is an infrared sensor.
[0025] As a preferred technical solution, the principle of extracting valid data from the parallel test results is: the parallel test results after removing the maximum value and the minimum value are used as valid data.
[0026] As a preferred technical solution, the formula is:
[0027] Adhesion force F = m•g / (V•X), where: m is the mass of the carrier plate, kg; g is the acceleration of gravity, 9.8N / kg; V is the surface area of the carrier plate, m 2 ; X is the comprehensive sliding time, s;
[0028] The comprehensive sliding time is obtained by the following formula, and the test results are retained to 0.01s;
[0029] X=(T1+T2+…T n )÷n×(20~40)%+( t1+t2+…t n )÷n×(60~80)%;
[0030] Where: t1, t2…t n : The sliding time of the effective data of the metal plate, s; T1, T2…T n : The sliding time of the concrete slab valid data, s; n is the number of valid data; when the maximum and minimum values in the valid data exceed the average value by 50%, the test results of this group are invalid.
[0031] Preferably, the comprehensive sliding time is obtained by the following formula:
[0032] X=(t1+t2+t3)÷3×30%+(T1+ T2+ T3)÷3×70%;
[0033] Wherein: t1, t2, t3: sliding time of three groups of valid data of metal plates, s; T1, T2, T3: sliding time of three groups of valid data of concrete slabs, s; n is the number of valid data; when the maximum and minimum values in the valid data exceed the average value by 50%, the test results of this group are invalid.
[0034] In order to overcome the problem that the adhesion test results obtained by the existing testing device are of low reliability when used to characterize the actual application conditions, the inventor provides the above-mentioned test method that can conveniently and quickly test the adhesion of the shield tail grease. The method obtains the comprehensive sliding time by using a specific shield tail grease adhesion performance test device, and then calculates the adhesion of the shield tail grease based on a formula to evaluate whether the shield tail grease sample can be used for shield construction. The method is simple and avoids the use of expensive instruments that increase the development cost of the shield tail grease. The device is easy to obtain and simple to assemble, and has extremely high promotion and application value.
[0035] Furthermore, based on the test method provided by the present invention, by comprehensively controlling the shape and specifications of the carrier plate and the test plate, as well as the coverage area and mass of the oil sample to be tested on the surface of the carrier plate, and further coordinating the control of pressure and bonding conditions, the test results have high precision and good repeatability.
[0036] Finally, the subsequent adhesion test results were obtained by calculating the comprehensive sliding time through a formula based on the time it took for the adhesive plate to slide off the surface of the metal plate and the concrete plate, thereby improving the reliability of the adhesion test results and effectively evaluating the adhesion performance of the shield tail grease in actual construction conditions (tunnel excavation), providing a low-cost and high-reliability evaluation method for the development of shield tail grease products.
[0037] On the other hand, the present invention provides a shield tail grease adhesion performance testing device, comprising a supporting back plate, a test plate, a carrier plate, a propulsion splint, a cylinder, an electromagnetic device, an infrared sensor, a timer, a bottom plate, a first supporting plate, and a second supporting plate, wherein the test plate is detachably connected to the supporting back plate, the carrier plate is adsorbed and fixedly connected to the propulsion splint, a cylinder is provided at the other end of the propulsion splint, the lower ends of the left and right parts of the cylinder are respectively connected to the upper end of the first support plate and the upper end of the second support plate, the lower end of the first support plate and the lower end of the second support plate are fixed on the bottom plate, and a pressure gauge is provided on one side of the second support plate for obtaining the pressure of the cylinder; an infrared sensor is provided on the left side of the first support plate, and a timer is provided on the front side of the first support plate, the infrared sensor and the timer are connected by a wire, and the detection end of the infrared sensor is perpendicular to the direction of the test plate; the electromagnetic device is provided on the bottom plate, the electromagnetic device and the propulsion splint are connected by an electromagnetic conduction line, and an electromagnetic induction lamp is provided at the front end of the electromagnetic device for characterizing the switch of the electromagnetic device.
[0038] The test method provided by the present invention requires at least 500g of shield tail grease sample; the temperature control accuracy of the constant temperature box is 1°C; the weighing range of the balance meets 500g, and the accuracy reaches 0.1g; the timer accuracy is 0.1s.
[0039] Beneficial Effects
[0040] 1. The present invention provides a method for testing the adhesion performance of shield tail grease, which effectively overcomes the problem of low reliability of adhesion test results obtained by existing testing devices when used to characterize actual application conditions. The method is simple, easy to operate, highly accurate, and repeatable, and can be widely promoted and applied.
[0041] 2. The method of the present invention obtains the comprehensive sliding time by adopting a specific shield tail grease adhesion performance testing device, and then calculates the adhesion of the shield tail grease based on a formula to evaluate whether the shield tail grease sample can be used for shield construction. The method is simple and avoids the use of expensive instruments that increase the development cost of the shield tail grease. The device is easy to obtain and simple to assemble, and has extremely high promotion and application value.
[0042] 3. Based on the test method provided by the present invention, by comprehensively controlling the shape and specifications of the carrier plate and the test plate, as well as the coverage area and mass of the grease sample to be tested on the surface of the carrier plate, and further coordinating the control of pressure and lamination conditions, the test results have high precision and good repeatability.
[0043] 4. The subsequent adhesion test results are obtained by calculating the comprehensive sliding time from the sliding time of the adhesive plate from the metal plate and the concrete plate through a formula, thereby improving the reliability of the adhesion test results, effectively evaluating the adhesion performance of the shield tail grease in actual construction conditions (tunnel excavation), and providing a low-cost and high-reliability evaluation method for the development of shield tail grease products.
[0044] 5. The method provided by the present invention can be used for quality evaluation between different Dunwei grease products or different batches of the same product, and can also be used for comparative evaluation of Dunwei grease products of different models, and has high practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a schematic diagram of the structure of the shield tail grease adhesion performance testing device provided in Example 1. Figure 1 Middle: supporting back plate 1, testing plate 2, carrier plate 3, pushing clamp plate 4, cylinder 5, electromagnetic device 6, infrared sensor 7, timer 8, bottom plate 9, first supporting plate 10, second supporting plate 11, pressure gauge 12, electromagnetic induction lamp 13. DETAILED DESCRIPTION
[0046] Example 1
[0047] Embodiment 1 of the present invention provides a method for testing the adhesion performance of shield tail grease, comprising the following steps:
[0048] (1) Prepare the grease sample to be tested and the test device, and fix the test plate on the supporting back plate;
[0049] (2) Pre-treating the oil sample to be tested at a constant temperature and then scraping it onto the surface of the carrier plate to obtain an adhesive plate, and then fixing the adhesive plate on the advancing clamping plate;
[0050] (3) Control the pressure to make the adhesive plate fixed on the pushing clamp plate fit with the test plate fixed on the supporting back plate;
[0051] (4) Record the time it takes for the adhesive plate to slide off the surface of the test plate;
[0052] (5) Clean the adhesion plate and the test plate, repeat steps (2) to (5), and perform parallel testing 5 times;
[0053] (6) Extract valid data from the parallel test results and calculate the adhesion performance of the grease sample to be tested based on the formula.
[0054] The test plates are metal plates (stainless steel plates) and concrete plates.
[0055] The size of the stainless steel plate is: 300mm×540mm×10mm.
[0056] The dimensions of the concrete slab are: 300mm×540mm×10mm.
[0057] Before testing, the concrete slab is immersed in water until the surface is moistened. Before the metal slab and the concrete slab are attached to the adhesive slab, a water spray bottle is used to evenly wet the side where the metal slab and the concrete slab are attached to the adhesive slab.
[0058] The constant temperature pretreatment is as follows: placing the oil sample to be tested in a constant temperature box and controlling the temperature to be 20±3°C for 4 hours.
[0059] The carrier plate and the test plate have the same shape, both of which are rectangular parallelepipeds.
[0060] The ratio of the area of the carrier plate to the bonding surface of the test plate is 1:6.
[0061] The carrier plate has a size of 50 mm×90 mm×10 mm, a net weight of 350 g, and an allowable error of 5‰.
[0062] The surface of the carrier plate is completely covered with the grease sample to be tested, and the thickness of the grease sample to be tested covered on the surface of the carrier plate is uniform.
[0063] The ratio of the mass of the oil sample to be tested covered on the surface of the carrier plate to the mass of the carrier plate is 2:35.
[0064] The adhesion plate and the pushing splint are fixed by adsorption, specifically by magnetic adsorption.
[0065] The propulsion splint is a magnetic propulsion splint, and the carrier plate is made of a steel plate.
[0066] In the step (3), the pressure is controlled to be 7±0.3 kg.
[0067] The bonding time in step (3) is 5 seconds.
[0068] The time for the adhesive plate to slide off the surface of the test plate is recorded by a timer connected to the infrared detection device. The timer starts at the time when the pressure is controlled to 0 after step (3) is completed, and the magnetic button of the push clamp is closed, so that the adhesive plate and the test plate are connected only by the adhesion force of the grease sample to be tested. After that, the adhesive plate and the test plate lose their surface viscosity and slide off the infrared detection device. At this time, the timer stops and the time for the adhesive plate to slide off the surface of the test plate is obtained.
[0069] The infrared detection device is an infrared sensor.
[0070] The principle of extracting valid data from the parallel test results is: the parallel test results after removing the maximum value and the minimum value are used as valid data.
[0071] The formula is:
[0072] Adhesion force F=m•g / (V•X), where: m is the mass of the carrier plate (kg), g is the acceleration of gravity (9.8N / kg), and V is the surface area of the carrier plate (force-bearing area, ㎡).
[0073] The comprehensive sliding time is obtained by the following formula, and the test results are retained to 0.01s
[0074] X=(t1+t2+t3)÷3×30%+(T1+ T2+ T3)÷3×70%;
[0075] Where: t1, t2, t3: sliding time of three sets of valid data of metal plates, s;
[0076] T1, T2, T3: sliding time of three sets of effective data of concrete slab, s;
[0077] When the maximum and minimum values of the three groups of valid data exceed the average value by 50%, the test results of this group are invalid.
[0078] See also Figure 1On the other hand, embodiment 1 of the present invention provides a shield tail grease adhesion performance testing device, including a support back plate 1, a test plate 2, a carrier plate 3, a propulsion splint 4, a cylinder 5, an electromagnetic device 6, an infrared sensor 7, a timer 8, a bottom plate 9, a first support plate 10, and a second support plate 11, wherein the test plate 2 is detachably connected to the support back plate 1, the carrier plate 3 is adsorbed and fixedly connected to the propulsion splint 4, and the other end of the propulsion splint 4 is provided with a cylinder 5, and the lower ends of the left and right parts of the cylinder 5 are respectively connected to the upper end of the first support plate 10 and the upper end of the second support plate 11, and the first support plate 1 0 and the lower end of the second support plate 11 are fixed on the bottom plate 9, and a pressure gauge 12 is provided on one side of the second support plate 11 for obtaining the pressure of the cylinder 5; an infrared sensor 7 is provided on the left side of the first support plate 10, and a timer 8 is provided on the front side of the first support plate 10, and the infrared sensor 7 and the timer 8 are connected by a wire, and the detection end of the infrared sensor 7 is perpendicular to the direction of the test plate 2; an electromagnetic device 6 is provided on the bottom plate 9, and the electromagnetic device 6 is connected to the propulsion clamping plate 4 by an electromagnetic conduction line, and an electromagnetic induction lamp 13 is provided at the front end of the electromagnetic device 6 for indicating the switch of the electromagnetic device.
[0079] The test method provided by the present invention requires at least 500g of shield tail grease sample; the temperature control accuracy of the constant temperature box is 1°C; the weighing range of the balance meets 500g, and the accuracy reaches 0.1g; the timer accuracy is 0.1s.
[0080] The test method provided in Example 1 was used to test different batches of sample A. The test results are shown in Table 1.
[0081] Table 1
[0082]
[0083] Table 1 (continued)
[0084]
[0085] Repeated testing was performed on product batch numbers NT1240100019 and NT1240301621. See Table 2 for the test results.
[0086] Table 2
[0087]
[0088] The data in Tables 1 and 2 show that: (1) the differences in repeated test results of the same batch of products are small, proving that the method has good repeatability; (2) there are differences in the test results of different batches of the same product, proving that the product formulas of different batches fluctuate. The results of the NT1240100144 batch of products are quite different from those of other batches. The subsequent analysis of the formula is due to the increase in the proportion of a sol raw material in the formula. The short sliding time and high adhesion of the NT1240301621 batch are due to the short stirring time of the process parameters, resulting in the fibers not being evenly dispersed in the product. Therefore, this method can be used for the control of production process parameters in the development of shield tail grease formula and the quality evaluation of different batches of products.
[0089] The test method provided in Example 1 was used to test different batches of sample B. The test results are shown in Table 3.
[0090] Table 3
[0091]
[0092] The test method provided in Example 1 was used to test different batches of sample C. The test results are shown in Table 4.
[0093] Table 4
[0094]
[0095] The test method provided in Example 1 was used to test sample D and commercially available sample E. The test results are shown in Table 5.
[0096] Table 5
[0097]
[0098] The performance test results of Table 1, Table 3, Table 4 and Table 5 show that product B has better adhesion than product A, product C, product D and commercially available product E, thus providing guidance for the development of shield tail grease formula.
[0099] Performance Testing
[0100] Verification of method reliability: The reliability of the method was verified by water spray resistance data. In theory, the smaller the water spray resistance data, the better the adhesion. Product A (NT1240100167) and product C (NT1240100319) were tested for water spray resistance (refer to SH / T 0643-1997 Determination of water spray resistance of lubricating grease). The actual test data of the batch water spray resistance of product A (NT1240100167) was 1.12%, and the actual test data of the batch water spray resistance of product C (NT1240100319) was 1.73%, that is, NT1240100167 has better adhesion to NT1240100319. By comparing the adhesion test results of NT1240100167 to NT1240100319 obtained in Example 1, the adhesion test result of NT1240100167 was 13.02N / m 2 *s, the adhesion test result of NT1240100319 is 19.18N / m 2 *s, the adhesion test result of NT1240100167 is smaller than that of NT1240100319, and the adhesion is better. The above results prove that the scheme of the present invention is reliable.
Claims
1. A method for testing the adhesion performance of shield tail grease, characterized in that: At least the following steps are included: (1) Prepare the oil sample to be tested and the test device, and fix the test plate on the supporting back plate; (2) Pre-treating the oil sample to be tested at a constant temperature and then scraping it onto the surface of the carrier plate to obtain an adhesive plate, and then fixing the adhesive plate on the advancing clamping plate; (3) Control the pressure to make the adhesive plate fixed on the pushing clamp plate fit with the test plate fixed on the supporting back plate; (4) Record the time it takes for the adhesive plate to slide off the surface of the test plate; (5) Clean the adhesion plate and the test plate, repeat steps (2) to (5), and perform parallel tests 4 to 6 times; (6) Extract valid data from the parallel test results and calculate the adhesion performance of the grease sample to be tested based on the formula; the constant temperature pretreatment is: put the grease sample to be tested in a constant temperature box and control the temperature to 20±3℃ for at least 3h; the carrier plate and the test plate have the same shape, both are rectangular; the test plate is a metal plate and a concrete plate; the ratio of the area of the carrier plate and the test plate bonding surface is 1: (5-10), the area of the surface of the carrier plate covered with the grease sample to be tested accounts for more than 1 / 2 of the area of the carrier plate, and the ratio of the mass of the grease sample to be tested on the surface of the carrier plate to the mass of the carrier plate is (1-3): (30-40); the adhesion plate and the push splint are fixed by adsorption, specifically by magnetic adsorption, the push splint is a magnetic push splint, and the material of the carrier plate is The material can be adsorbed and fixed by the magnetic push clamp; the control pressure in step (3) is 6-8kg, and the bonding time in step (3) is 3-10s; the time when the adhesive plate slides off the surface of the test plate is recorded by a timer connected to the infrared detection device, and the time when the timer starts is when the control pressure is 0 after step (3) is completed, and the magnetic button of the push clamp is closed, so that the adhesive plate and the test plate are connected only by the adhesion force of the grease sample to be tested, and then the adhesive plate and the test plate slide off the infrared detection device because the grease sample to be tested loses its surface viscosity, and the timing is stopped at this time, and the time when the adhesive plate slides off the surface of the test plate is obtained; the principle of extracting valid data from the parallel test results is: the parallel test results after removing the maximum and minimum values are used as valid data; the formula is: Adhesion force F = m•g / (V•X), where: m is the mass of the carrier plate, kg; g is the acceleration of gravity, 9.8N / kg; V is the surface area of the carrier plate, m 2 ; X is the comprehensive sliding time, s; The comprehensive sliding time is obtained by the following formula, and the test results are retained to 0.01s; X=( T1+T2+…T n )÷n×(20~40)%+( t1+t2+…t n )÷n×(60~80)%; Where: t1, t2…t n : The sliding time of the effective data of the metal plate, s; T1, T2…T n : The sliding time of the concrete slab valid data, s; n is the number of valid data; when the maximum and minimum values in the valid data exceed the average value by 50%, the test results of this group are invalid.